Consitutional Complaint dalam Rekonseptualisasi Kewenangan Mahkamah Konstitusi Republik Indonesia - Wafa Nihayati Inayah; H Muhamad Rezky Pahlawan MP (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The constitutional court in Indonesia, namely the Constitutional Court of the Republic of Indonesia, does not yet have the authority to handle cases with the object of constitutional complaint, but in practice there are many applications that are actually constitutional complaint cases packaged in judicial review applications. Judicial Review in the field of the Constitution, is a review and/or test by a state power body to be able to cancel the decision of the law-making body (legislation) and/or the government body (executive). Judicial Review in this field in Indonesia is the competence of the Constitutional Court. With no authority owned by the Constitutional Court, which then became the reason for not accepting the application, of course it was felt that there was a need for an expansion of authority. So that the protection of the constitutional rights of citizens for violations committed by state administrators is true. This is in line with the Constitutional Court as the guardian of the constitution. In this study, the author uses a normative juridical research method. Normative legal research views that the study of legal norms, legal principles, legal systematics, and comparative law, is a mandatory part to be studied in relation to the authority of the constitutional court in judicial review.